Analisis Dampak Perubahan Kerapatan Hutan Di Kabupaten Muna - Buransa, Silfiani, Dr. Kuswaji Dwi Priyono, M.Si, Jumadi, S.Si. M.Sc (2015)
Forest damage in Muna Regency Southeast Sulawasi has reached a critical point. Based on data from Muna Regency Department of Forestry, the size of teak forest in Muna today is approximately 500 ha compared with 60.000 ha in 1970-s. This study aims to clarify and analyze forest density level in Muna Regency Southeast Sulawesi in 2007 and 2009, present information on the decline of forest density in every sub-district in Muna Regency Southeast Sulawesi, and discover the impacts of forest damage in Muna Regency Southeast Sulawesi. Forest density levels in 2007-2009 were classified by processing the images of Landsat TM using NDVI (Normalized Different Vegetation Index) formula which utilizes band 3 and band 4. Changes of forest density in 2007-2009 were calculated by matching method and calculated by software ArcGIS. Forest damage impact analysis was performed without checking the and only based on information stakeholders The results showed that the highest forest density in Muna regency in 2007 was in Bonegunu Sub-district and in 2009 was in Tongkuno Sub-district. Based on the processing result of forest density level in Muna regency, in 2007 the size was 144.694,2 ha, while in 2009 it was 78.007 ha. Based on the data it can be seen that the size of the forest in Muna Regency declined by 66.957,2 ha largely in Tungkuno Sub-district. Forest damage in Muna Regency ecologically impacted the extinction of a primate called Macaca ochreata brunnescens, temperature change in Muna Regency which continues to rise and increase of dengue fever cases, increase of poverty, and natural disasters such as drought, landslide, flood, and declining water quality.